Hydrothermal Alteration and Geochemical Signatures of High-Sulfidation Epithermal Gold Mineralization in Petai Patah, West Kalimantan, Indonesia - Hede, Arie Naftali Hawu; Azmi, Noprizan; Syafrizal (UIR PRESS, 2026)
High-sulfidation epithermal systems are an important source of precious metals in volcanic-arc settings, yet detailed studies of these systems in the Schwaner Mountains of western Borneo remain scarce. This study investigates the hydrothermal alteration and geochemical signatures of high-sulfidation epithermal gold mineralization in the Petai Patah area, Ketapang District, West Kalimantan, Indonesia, hosted within the Cretaceous Sukadana Granite and the Paleogene Kerabai Volcanic Complex. An integrated analytical approach was employed, combining reflectance spectroscopy, petrographic analysis, X-ray diffraction (XRD), and whole-rock geochemistry on 15 representative rock samples from surface outcrops and drill cores. Results reveal a well-defined hydrothermal alteration zonation, comprising an advanced argillic core (alunite, pyrophyllite, dickite) in Pit Lokma, surrounded by a phyllic zone (dominant muscovite/sericite–illite–pyrite assemblage) extending into Pit Limun. Gold mineralization (maximum 1.61 ppm Au in sample DC 347, Pit Limun) is spatially correlated with these alteration zones and occurs in association with sulfide minerals, suggesting a structurally controlled fluid pathway. Elevated As concentrations in gold-bearing samples from Pit Limun, together with the diagnostic mineralogical assemblage, support the interpretation of a high-sulfidation epithermal system. This study provides new insights into the spatial relationship between alteration zonation and gold enrichment within a high-sulfidation epithermal system, offering implications for mineral exploration in similar magmatic arc settings across Southeast Asia.